Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/978-3-319-19006-8_33
|View full text |Cite
|
Sign up to set email alerts
|

A Fuzzy Multi-objective Model with MFCA Approach for Selecting Products Variety in a Textile Supply Chain

Abstract: Offering product variety is one of the strategies for today's competitive advantage. In spite of the fact that greater product variety allows manufacturers to meet a larger share of customer's satisfaction, it increases the complexity of the process and reduces efficiency of the operational performance in a supply chain. Increasing product variety also creates more wastes and more losses, and reduces efficiency of resources. In this chapter, a fuzzy multi-objective model is developed in an imprecise environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Increasing productivity has been defined as the core strategy of green productivity, cleaner production, sustainable engineering, lean production, and the like [3][4][5][6]. The Sustainable Development Goals (SDGs) also require responsible and sustainable production patterns for doing more with less resources such that a business can help improve the potential of resource and cost savings by identifying hotspots of environmental and economic impacts within the value chain [7].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing productivity has been defined as the core strategy of green productivity, cleaner production, sustainable engineering, lean production, and the like [3][4][5][6]. The Sustainable Development Goals (SDGs) also require responsible and sustainable production patterns for doing more with less resources such that a business can help improve the potential of resource and cost savings by identifying hotspots of environmental and economic impacts within the value chain [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are few studies using the MFCA technique for the garment industry. The relevant studies are the research of Kasemset and Chernsupornchai [24], who applied MFCA in SMEs which showed the effective result in cost-saving; and the research of Amid et al [25], who developed a fuzzy weighted max-min multi-objective model to reduce waste and response to environmental requirements. For this reason, there is a possibility in the garment industry to investigate and improve the manufacturing process to enhance the performance, along with mitigating environmental impact by implementing MFCA with management tools, which will be presented in the next chapter.…”
mentioning
confidence: 99%